Cellular crosstalk between airway epithelial and endothelial cells regulates barrier functions during exposure to double‐stranded RNA. Issue 1 (18th January 2017) - Blume, Cornelia; Reale, Riccardo; Held, Marie; Loxham, Matthew; Millar, Timothy M.; Collins, Jane E.; Swindle, Emily J.; Morgan, Hywel; Davies, Donna E.
Abstract: Introduction: The epithelial and endothelial barriers of the airway mucosa are critical for regulation of tissue homeostasis and protection against pathogens or other tissue damaging agents. In response to a viral infection, epithelial cells must signal to the endothelium to initiate immune cell recruitment. This is a highly temporal regulated process; however, the mechanisms of this cross‐talk are not fully understood. Methods: In a close‐contact co‐culture model of human airway epithelial and endothelial cells, cellular crosstalk was analyzed using transepithelial electrical resistance (TER) measurements, immunofluorescence, electron microscopy, and ELISA. Viral infections were simulated by exposing airway epithelial cells apically to double‐stranded RNA (Poly(I:C)). Using a microfluidic culture system, the temporal release of mediators was analyzed in the co‐culture model. Results: Within 4 h of challenge, double‐stranded RNA induced the release of TNF‐α by epithelial cells. This activated endothelial cells by triggering the release of the chemoattractant CX3 CL1 (fractalkine) by 8 h post‐challenge and expression of adhesion molecules E‐selectin and ICAM‐1. These responses were significantly reduced by neutralising TNF‐α. Conclusion: By facilitating kinetic profiling, the microfluidic co‐culture system has enabled identification of a key signaling mechanism between the epithelial and endothelial barriers. Better understanding of cell–cell cross‐talk and its regulatory mechanisms has the potential to identify new therapeutic strategies to control airway inflammation. Abstract : Using a microfluidic in vitro co‐culture model we show that human airway epithelial cells activate the endothelial barrier by releasing TNF‐α resulting in CX3 CL1 release and expression of adhesion molecules. By facilitating kinetic profiling, the microfluidic co‐culture system has enabled identification of temporal signaling events between the epithelial and endothelial barriers. Better understanding of cell–cell cross‐talk and its regulatory mechanisms has the potential to identify new therapeutic strategies to control airway inflammation.